PENGARUH IKLIM ORGANISASI, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK SUMATERA UTARA I - Kristina Romauli (Universitas Islam Sumatera Utara, 2020)
The formulation of the problem in this research is how the influence of organization climate on employees performance. How influence of work motivation on employees performance. How influence of work satisfaction on employees performance. How influence of organization climate, work motivation and work satisfaction on employees performance. The purpose of this research is for know influence and analize of organization climate on employees performance. For know influence and analize of work motivation on employees performance. For know influence and analize work satisfaction on employees performance. For know influence and analize organization climate, work motivation and work satisfaction on employees performance. The sample in this research is 95 employees, with data analysis technique used is multiple linear regression analyze. The results of this research explain that organization climate effect has a positive and significant on employee performance. Work motivation effect has a positive and significant on employee performance. work satisfaction effect has a positive and significant on employee performance. Organization climate, work motivation and work satisfaction effect have a positive and significant on employee performance.